Changes in the Norwegian Sea deep water - Østerhus, Svein; Blindheim, Johan; Turrell, William R.; Hansen, Bogi; van Bennekom, Aleido Johannes (ICES, 1996)
This paper deals with observed changes in the Norwegian Sea Deep Water (NSDW) after the cessation of bottom water formation in the Greenland Sea. Current measurements indicate that the deep water flow from the Greenland Sea to the Norwegian Sea has reversed. The Deep Water in the Norwegian Sea is warming in the entire layer below 1000m depth and down to the bottom. The thickness of the adiabatic layer is decreasing. The salinity of the homohaline layer is constant but the thickness is decreasing. The overflow water in the Faroe-Shetland Channel is freshening.